Laporan kasus : Tatalaksana stenosis pulmonal kritis pada anak usia 12 bulan dengan Valvuloplasti Balon Transkateter Perkutan - Dyahris Koentartiwi (Warmadewa University, 2021)
Abstract Critical pulmonary stenosis (PS) is used in infants born with very severe narrowing valves and requires treatment soon after birth. At four months old, an A-12-month-old boy was diagnosed with critical pulmonary stenosis but still successfully managed by percutaneous transluminal balloon valvuloplasty (PTBV) with satisfactory results without serious complications. Since he was born, cyanosis was seen at his lips and fingertip, with oxygen saturation around 60% until 70%. Echocardiography showed critical pulmonary stenosis, atrial septal defect (ASD), and patent ductus arteriosus (PDA). Percutaneous transluminal balloon valvuloplasty (PTBV) is accepted as the treatment of choice for critical pulmonary valve stenosis in many centers worldwide with significant results. After PTBV, he experienced improvement condition as no cyanosis was observed and oxygen saturation was 96%. This case was our first PTBV intervention case in our hospital and gave satisfactory results, although the intervention was delayed due to our limited resources before. Keywords: cyanosis, critical pulmonary stenosis, percutaneous transluminal balloon valvuloplasty